The economic adjustment programme for Portugal. Fifth review - Summer 2012 (Luxembourg, 2012)
"A joint Commission/ECB/IMF mission met with the Portuguese authorities in Lisbon from 28 August to 11 September 2012 to assess compliance with the terms and conditions of the Portuguese Adjustment Programme. This report provides an assessment of compliance and summarises the findings of the mission. Raising competitiveness, employment and the growth potential of the economy remains of crucial importance for the success of the Programme. Overall, Programme implementation remains solid, but important risks and challenges are lying ahead. The revised fiscal adjustment path with new deficit targets of 5% of GDP in 2012, 4.5% of GDP in 2013 and 2.5% of GPD in 2014, coupled with additional fiscal measures planned for 2013-2014 should keep fiscal consolidation on track. But risks and challenges derive from several areas. The macro-economic outlook may be affected by the continued tensions in the euro area. Fiscal adjustment has moved more strongly towards the revenue side in the short run. In a forward-looking perspective, the composition of consolidation measures should be rebalanced towards the expenditure side which is more conducive to medium-term growth. Finally, consensus-building is paramount for a successful implementation of the Programme. The Programme's financing envelope remains sufficient. Approval of the conclusions of this review will allow the disbursement of EUR 4.3 billion (EUR 2.8 billion by the EU and EUR 1.5 billion by the IMF) in October 2012, bringing the total amount disbursed to Portugal to EUR 61.4 billion of the overall Programme envelope amounting to EUR 78 billion "